2019
DOI: 10.1111/hiv.12699
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of airflow obstruction in an HIV tertiary care clinic in Montreal, Canada: a cross‐sectional study

Abstract: Objectives The reported prevalence of chronic obstructive pulmonary disease ( COPD ) in people living with HIV ( PLWHIV ) varies widely. Our objective was to estimate the prevalence of airflow obstruction and COPD in unselected PLWHIV and identify characteristics that increase the risk of nonreversible airflow obstruction in order to guide case finding strategies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…However, despite early ART, our results indicated that, contrary to the liver, several gene transcripts associated with the acute-phase response, coagulation, and complement remain elevated in the lungs. This persistent alteration of gene expression could contribute to the tissue damage observed in PLWH ( 95 ). Serpins are important regulators of extracellular matrix remodeling, contributing to lung pathology, such as COPD and cystic fibrosis ( 46 ), while tissue factor drives coagulopathy ( 96 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite early ART, our results indicated that, contrary to the liver, several gene transcripts associated with the acute-phase response, coagulation, and complement remain elevated in the lungs. This persistent alteration of gene expression could contribute to the tissue damage observed in PLWH ( 95 ). Serpins are important regulators of extracellular matrix remodeling, contributing to lung pathology, such as COPD and cystic fibrosis ( 46 ), while tissue factor drives coagulopathy ( 96 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that baseline current smoking and more pack-years of smoking were associated with the low baseline, slow decline FEV 1 trajectory, moderate decline and rapid decline FEV 1 /FVC trajectories, and baseline low DL CO trajectory. Current smoking and pack-years of smoking have been identified as independent predictors of airflow and diffusion impairment in cross-sectional studies (4,7,21,37,(46)(47)(48) and of faster decline in pulmonary function in longitudinal cohorts (14,21,37,38). Our study, which integrates baseline and longitudinal data to identify lung function trajectories and has longer follow-up (median, 8.1 yr vs. 1.5-6.3 yr in earlier cohorts), provides additional evidence on the detrimental relationship between smoking and lung function in PWH.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have evaluated different screening approaches, no conclusive recommendations can be made regarding COPD screening and diagnosis in PWH at this time. 150,[153][154][155][156] For example, a group in Canada offered screening spirometry to all patients in an HIV clinic; 156 notably, less than a third of the invited participants agreed to participate, and only 11% had airflow obstruction.…”
Section: Diagnosis and Clinical Findings Of Copd In Pwh Screening And...mentioning
confidence: 99%